Exploring the Limitations on RFID Technology in Traceability Systems at Beverage Factories - Isabel Expósito; Iñigo Cuiñas (International Journal of Antennas and Propagation)
The application of RFID in traceability of products in beverage factories is analyzed in terms of the electromagnetic conditions defined by the massive presence of metallic elements and liquids. Various experiments are reported to determine the maximum reading range from RFID tags installed on tanks or to read RFID information around bottles, both empty and full of wine, trying to put in context the possible problems that could appear when installing an RFID-based traceability system within a winery, a brewery, or any other beverage factory.